2014
DOI: 10.1155/2014/920275
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p53 Mutation and Mismatch Repair Proteins Dysregulation in NNK-Induced Malignant Transformation of Human Bronchial Epithelial Cells

Abstract: Genome integrity is essential for normal cellular functions and cell survival. Its instability can cause genetic aberrations and is considered as a hallmark of most cancers. To investigate the carcinogenesis process induced by tobacco-specific carcinogen NNK, we studied the dynamic changes of two important protectors of genome integrity, p53 and MMR system, in malignant transformation of human bronchial epithelial cells after NNK exposure. Our results showed that the expression of MLH1, one of the important MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…This latter result seems contradictory because, recently, the tumor-suppression activity of p53 has been reported to be involved in the regulation of cystine metabolism, and p53 exerts its effect by repressing the expression of SLC7A11 and inducing ferroptosis (Jiang et al., 2015). However, previous studies investigating mouse models have suggested that iron excess might negatively regulate p53 signaling by both destabilizing the p53 protein and interfering with its DNA binding activity (Shen et al., 2014). Thus, we cannot exclude the possibility that p53 might progressively lose its ability to protect cells.…”
Section: Discussionmentioning
confidence: 99%
“…This latter result seems contradictory because, recently, the tumor-suppression activity of p53 has been reported to be involved in the regulation of cystine metabolism, and p53 exerts its effect by repressing the expression of SLC7A11 and inducing ferroptosis (Jiang et al., 2015). However, previous studies investigating mouse models have suggested that iron excess might negatively regulate p53 signaling by both destabilizing the p53 protein and interfering with its DNA binding activity (Shen et al., 2014). Thus, we cannot exclude the possibility that p53 might progressively lose its ability to protect cells.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism of HCV-induced oncogenesis seems to result from the interference of HCV proteins in the intracellular signal transduction processes via a mechanism including the dysregulation of cell cycle control[128]. In the presence of DNA damage, the P53 protein can be activated, promoting the expression of several important genes involved in cell cycle arrest, DNA repair, and apoptosis[129]. Accordingly, whether HCV infections occur concurrently with other genomic alterations, such as TP53 mutations, in hepatocarcinogenesis is of interest.…”
Section: Somatic Mutations In Hccmentioning
confidence: 99%
“…Cells maintain normal functions and survival via genome integrity. However, genome instability of cells causes genetic aberrations and is considered a hallmark of most types of cancer (14). After the presence of DNA damage, p53 protein can be activated to promote important gene expressions that are involved in cell cycle arrest, DNA repair and apoptosis (15).…”
Section: Curcumin Alters Gene Expression-associated Dna Damage Cell mentioning
confidence: 99%